Cost Optimization of the Medical Tourism Market Research Project in Poland and Turkey - CHMIELEWSKI, Mariusz; KUCZAMER-KŁOPOTOWSKA, Sylwia; BOGUSZEWICZ-KREFT, Monika; AYCI, Ali (Journal of Environmental Management and Tourism, 2021)
Research and development projects constitute a specific group of activities carried out in the course of scientific research. The purpose of this article was the analysis of the planned research and development project related to the research on medical services market in Poland and Turkey in the aspect of cost optimization. The analyzed project was designed to examine consumer behavior in the market of a new and growing tourism sector, i.e. medical tourism. Medical tourism is currently defined as the traveling of people to a foreign country in order to undergo planned treatment there, caused by financial or qualitative reasons or due to the unavailability of services in the country of residence. The aim of the planned research project was to compare the behavior of two different groups of stakeholders on two different markets - Polish and Turkish. Efficient implementation of a research project requires precise planning of all activities that should be conducted. The performed analysis showed that regardless of the location of the planned project, its schedule consists of similar components, but the time and costs associated with the project will be different and will largely depend on the location of the research. In the article, in order to optimize the basic parameters of a research project carried out in various destinations, a traditional project management tool, i.e. the Gantt chart, was used, and complemented with the cost gradient concept. The use of both those tools made it possible to identify activities, the change of which has the greatest impact on the cost and time optimization of the project in Poland and Turkey. The analysis of the research project carried out in various destinations showed that, regardless of the location of the research project, shortening its time is associated with a similar increase in the cost of the project, despite the fact that it concerns different activities in both analyzed cases. As a rule, the implementation of a project, including a research project, should be preceded by planning, which enables its subsequent optimization using traditional project management tools.